“I Listen, Yet Somehow I Do Not Understand”: The portrait of students’ perceived challenges in Listening class - Muzdalifah Mahmud; Moh. Mirza Er. Pateda; Helena Badu (EDUJ : English Education Journal, 2024)
Listening is a fundamental skill in language acquisition and learning, yet it is often perceived as one of the most challenging skills by students, as this is also the case with English language classes. Listening requires significant attention and concentration to comprehend material such as dialogues and monologues. The objective of this study is to gain insight into the perceptions of students in the English Department class of 2019 regarding the difficulties they encounter in developing listening skills, as well as the factors that contribute to these difficulties. Based on initial observations and previous research, key challenges have been identified including difficulties due to physical limitations, poor audio quality, unfamiliar accents, and limited vocabulary. A qualitative research method with a narrative inquiry design was employed to explore students' experiences through in-depth interviews. The findings indicate that students struggle with listening due to a number of factors, including poor audio quality, unfamiliar accents, and limited vocabulary. The study also highlights additional challenges arising from online learning during the COVID-19 pandemic and its impact on students' listening comprehension. These insights are expected to inform English language teaching practices to enhance the effectiveness of listening skills instruction.